Using honeypots to detect internal attacks at FTMSK / Muhamad Rizal Azali - Azali, Muhamad Rizal (2005)
This project is using a honeypot as a tool to detect internal network attack at Faculty of Information Technology and Quantitative Science, (FTMSK). The purpose of this project is to know how secure the FTMSK internal network is. Honeypots are used to detect attack that enables the automated detection from any malicious and unknown attack over the internal network. We classify the attack at the lecturer's computers by using different tools of honeypots and make analysis of it. This project is used the Windows platform as the operating system that match with the honeypots tools. We tested and compared among of many honeypots tools and concluded that KFsensor is the best honeypot tool. We also defined the advantages of used the different tools of the honeypot. The research found the internal network of FTMSK is secured and if connection made by other host will detect. This project also gave the information for lecturers to know how secured their computers are. IV